The library marketing toolkit - Potter, Ned 1980- (London Facet Publishing, 2012)
This practical guide offers coverage of every element of library marketing and branding for all sectors, including archives and academic, public and special libraries.
Introduction -- Seven key concepts for marketing libraries -- Strategic marketing -- The library brand -- Marketing and the library building -- An introduction to online marketing -- Marketing with social media -- Marketing with new technologies -- Marketing and people -- Internal marketing -- Library advocacy as marketing -- Marketing special collections and archives -- A final word on marketing libraries -- Appendix: Glossary of Web 2.0 tools and platforms.
Keywords: Libraries -- Marketing; Branding (Marketing) -- Libraries; Libraries -- Public relations; Advertising -- Libraries